Pertanggungjawaban Pidana Malpraktik Tenaga Medis dalam Mewujudkan Keadilan Pelayanan Kesehatan - Ghania Alya Haviza; Yovita Arie Mangesti (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Healthcare services inherently involve risks that cannot be entirely avoided, and when patients suffer harm, a fundamental legal question arises regarding the boundary between medical risk and malpractice subject to criminal liability. This ambiguity is compounded by the absence of an explicit definition of malpractice in Indonesia's positive law, including both the Criminal Code and Health Law Number 17 of 2023, resulting in inconsistency in judicial practice. This study aims to analyze the construction of criminal liability of medical personnel for malpractice based on the applicable legal framework in order to achieve a balance between legal protection for patients and legal certainty for medical personnel. A normative juridical method was employed using statutory, conceptual, and comparative legal approaches with Singapore. The findings indicate that criminal liability of medical personnel must be grounded in the principle of geen straf zonder schuld, requiring cumulative proof of criminal responsibility, fault in the form of intent or gross negligence, and the absence of excusing grounds. Medical risks arising from actions performed in accordance with professional standards do not constitute a basis for criminal liability. Clinical privilege and clinical appointment serve as juridical parameters determining the legitimacy of medical actions, while hospitals as corporate entities may also be held liable when patient harm originates from systemic failure, inadequate supervision, or deficient management policy. Criminal law in the context of medical malpractice must function as an ultimum remedium, prioritizing professional disciplinary mechanisms and alternative dispute resolution before criminal proceedings are pursued.